Sport-specific prevalence of relative energy deficiency in sport (REDs) risk among Finnish female national- and international-level athletes - Wynne-Ellis, M.; Kuljukka, A.; Mikkonen, R. S.; Hackney, A. C.; Heikura, I.; Hulmi, J.; Valtonen, M.; Ihalainen, J. K. (Journal of Science and Medicine in Sport, 2026)
Objectives To determine the prevalence of REDs risk and sport-specific patterns of REDs-related indicators in Finnish national- and international-level female athletes and active non-athletes.